PENINGKATAN KEMAMPUAN BERHITUNG PEMBAGIAN MELALUI METODE JARIMATIKA PADA SISWA KELAS III SD NEGERI 195 PAGARAN BARU KOTANOPAN - Almira Amir; Nuraisyah Nuraisyah (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Teachers who are less varied in teaching math can cause students to feel bored and saturated. The usual way teachers use is to memorize or remember the formula, so that burden the students' brains because the ability of each student is different in memorization. Based on the above background, this study aims to determine the extent to which the use of methods can improve the ability of arithmetic numeracy. The division of students in class III SD Negeri 195 Pagaran Baru Kecamatan Kotanopan. The type of research used is Classroom Action Research (PTK). The results showed that in the first cycle there was an increase in students' numeracy skills in the division of material from 47.36% or 9 students to 61.90% or 13 students with an increase of 14.54%. Results of reflection on the first cycle, the percentage of learning mastery less than 70% so that followed in cycle II. In the second cycle there was an increase of 73.68% or 14 students to 78.95% or 15 students with an increase of 5.26%. The results of reflection cycle II shows that with the use of the method of Jarimatika, the percentage of learning mastery has reached more than 70%, so there is an increase from cycle I to cycle II of 43.36%. Thus the use of the method of the finger can improve the ability to count The division of the students III SD Negeri 195 Pagaran Baru Kecamatan Kotanopan. Keywords: Jarimatic Method, Ability to Calculate Division.